Odpowiedzi

  • Użytkownik Zadane
2009-12-09T16:57:38+01:00
A) (x+2y=-2/-2y ( klamra
(2x-y=1 (

x=-2-2y
2(-2-2y)-y=1
-4-4y-y=1
-4-5y=1/+4
-5y=5/:(-5)
y=-1

x-2=2/+2
(x=4
( y=-1
Najlepsza Odpowiedź!
2009-12-09T17:22:23+01:00
A)x+2y=-2
2x-y=1

x=-2-2y
2(-2-2y)-y=1
x=-2-2y
-4-4y-y=1
x=-2-2y
-5y=5
x=-2-2y
y=-1
x=-2-2*1
y=-1
x=-4
y=-1
b)x+4y=-2
3x-8y=10
x=-4y-2
3(-4y-2)-8y=10
x=-4y-2
-12y-6-8y=10
x=-4y-2
-20y=16
y=4/5
x=-4*-4/5-2
y=-4/5
x=-3 1/5
c)x-2y=3
-2x+y=0
x=3+2y
-2(3+2y)+y=0
x=3+2y
-6-4y+y=0
x=3+2y
-3y=6
x=3+2y
y=-2
x=3+2*-2
y=-2
x=-1
d)2x+y=9
5x-4y=3
y=9-2x
5x-4(9-2x)=3
y=9-2x
5x-36+8x=3
y=9-2x
13x=39
y=9-2x
x=3
y=3
e)3x-2y=5
2x-y=4
3x-2y=5
-y=4-2x
3x-2y=5
y=-4+2x
3x-2(-4+2x)=5
y=-4+2x
3x+8-4x=5
y=-4+2x
-x=-3/(-1)
y=-4+2x
x=3
y=2
f)2x+9y=-9
-3x+3y=8
x=-4,5-4,5y
-3(-4,5-4,5y)+3y=8
x=-4,5-4,5y
13,5+16,5y=8
x=-4,5-4,5y
16,5y=5
x=-4,5-4,5y
y=3
x=18
dalej nie mam